2002
DOI: 10.1021/bi0261490
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mitochondrial ADP/ATP Carriers:  Kinetic Properties and Biogenesis of Wild-Type and Mutant Proteins in the Yeast S. cerevisiae

Abstract: The mitochondrial adenine nucleotide carrier, or Ancp, plays a key role in the maintenance of the energetic fluxes in eukaryotic cells. Human disorders have been found associated to unusual human ANC gene (HANC) expression but also to direct inactivation of the protein, either by autoantibody binding or by mutation. However, the individual biochemical properties of the three HAncp isoforms have not yet been deciphered. To do so, the three HANC ORF were expressed in yeast under the control of the regulatory seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 54 publications
3
74
0
Order By: Relevance
“…Moreover, it has been suggested that the ANT2 isoform, unlike ANT1, could import glycolytic ATP into mitochondria, and a differential regulation of ANT2 gene expression has also been demonstrated (30). However, it has also been reported that there are no important differences in the transport activity or kinetic parameters of ANT isoforms (31). In addition, deletion studies of ANT1 demonstrated that apoptosis induction by ANT1 does not depend upon its function as a mitochondrial carrier (13).…”
Section: Fig 4 P65(nf-b) Is Increased In Mitochondria From Ant1-ovementioning
confidence: 99%
“…Moreover, it has been suggested that the ANT2 isoform, unlike ANT1, could import glycolytic ATP into mitochondria, and a differential regulation of ANT2 gene expression has also been demonstrated (30). However, it has also been reported that there are no important differences in the transport activity or kinetic parameters of ANT isoforms (31). In addition, deletion studies of ANT1 demonstrated that apoptosis induction by ANT1 does not depend upon its function as a mitochondrial carrier (13).…”
Section: Fig 4 P65(nf-b) Is Increased In Mitochondria From Ant1-ovementioning
confidence: 99%
“…Mutations in a number of nuclear DNA (nDNA)-encoded mitochondrial proteins impair OXPHOS and cause cardiomyopathy (4). Recently, two case reports demonstrated homozygous solute carrier family 25, member 4 (SCL25A4) (adenine nucleotide translocator-1, ANT1) mutations (A123D; c.111+1G > A) (5,6) in patients who had cardiomyopathy and mitochondrial myopathy without the chronic progressive external ophthalmoplegia (CPEO) characteristic of certain autosomal dominant ANT1 missense mutations (L98P, A90D, D104G, A114P, and V289M) (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The protocols and materials used to perform isolation of mitochondria, ADP/ATP transport, [ 3 H]ATR binding experiments, cytochrome content measurements, and protein immunostaining are described in De Marcos et al (26). For determination of the relative ScAnc2p content mitochondria were isolated from cells grown in SGal-W.…”
Section: Chemicals-[mentioning
confidence: 99%
“…Import reactions were performed as described in Ref. 26. The samples were subjected to a 15% SDS-PAGE and the labeled proteins were visualized with the Fluorescent Image Analyzer Fujifilm FLA-500.…”
Section: Chemicals-[mentioning
confidence: 99%